Risk factors deciding the prevention and healing of diabetic foot ulcer: a prospective study in Chennai Medical College Hospital and Research Center Irungalur, Trichy, Tamil Nadu, India; a rural based tertiary medical care centre - Murugan, R.; Padma, S.; Senthilkumaran, M. (International Surgery Journal, 2018)
Background: Diabetic foot ulcer is the one among and the most common complication of diabetes mellitus patients. Various studies from over the world for the past 2 decades discuss the important risk factors that decide the prevention and outcome of diabetic foot ulcer. In our prospective study we have discussed the risk factors focused on prevention and treatment of diabetic foot ulcer in a rural tertiary medical care centre. Methods: Totally 940 patients with the clinical diagnosis of diabetic foot ulcer admitted in our hospital surgical department were studied prospectively with their clinical symptoms and signs of diabetic foot ulcer and various evaluations done for the comorbid conditions with the help of other specialty departments. All these risk factors studied in our rural based tertiary medical centre were collected in a designed format were studied and discussed in comparison to the chosen data available in various studies done at various countries. Results: All the 940 patients admitted for diabetic foot ulcer who underwent a methodical evaluation for risk factor showed an elevated HbA1c more than 8 in 720 (77.5%) patients, bony involvement like osteomyelitis in 274 patients (29%) , peripheral vascular disease in 421 (44.9%), neuropathy in 533 patients (56.7%), nephropathy 163 (17.34%), retinopathy in 102 (10.85%) and heart disease in 375 (39.89%). Conclusions: Proper protocols to the prevention and management of foot ulcer in diabetic patients have not reached many health care centres and it is imperative to stress on the related comorbid risk factors which influence the prevention and healing of diabetic foot ulcer. Present study done at a rural tertiary health care centre is mainly focused on the incidence of risk factors which modulates and modify the diabetic foot ulcer prevention and management. This study aims to support the health professionals to identify the risk factors apart from the clinical picture of diabetic foot ulcer that may enhance the efficient management and avoid the unnecessary morbidity and mortality.